Self-Actualization‟s influence on Job Satisfaction among Academic Leaders in Tamil Nadu Universities- A Review - GOPINATH, Dr. R. (The journal of contemporary issues in business and government, 2021)
In recent days, the distinction of job satisfaction is receiving increase attention in varied paradigms. Amongst, the job satisfaction of academic leaders is relatively significant to the improved and empowered future generations. Job Satisfaction is a vital determinant and a leading cause, for the successful endeavor of an organization and educational institutions, in the competitive edge. Consequently, many investigations reported that exercising appropriate management of human resource; offers sustain beneficial impacts, both in individuals and diverse organizational levels. These observed implications were, similar, in academic sector also the positive and few negative outcomes were well outlined in absence of job satisfaction in earlier investigations. As job satisfaction do mine provides, uncountable benefits to the organizations, employers strive to generate satisfaction among employees. Recent studies have evident and elucidated that Self-actualization has influenced and played a role, in determining the job satisfaction among the individuals. This review attempted to analyze the chronological recent literature on Self-Actualization’s influences on job satisfaction, among the academic leaders in Tamil Nadu Universities context.